2018
DOI: 10.1111/trf.14532
|View full text |Cite
|
Sign up to set email alerts
|

Apheresis buffy coat collection without photoactivation has no effect on apoptosis, cell proliferation, and total viability of mononuclear cells collected using photopheresis systems

Abstract: BACKGROUND Extracorporeal photopheresis (ECP) has been approved for the treatment of advanced cutaneous T‐cell lymphoma since 1988. While the precise mechanisms resulting in clinical effects are not fully understood, the photoactivation of mononuclear cells (MNCs) using ultraviolet A (UVA) light and methoxsalen is believed to be the predominant initiating process. The effects of MNC passage through the instrument without photoactivation are unknown. The objective of this study was to evaluate the effect of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
5
3
0
4
Order By: Relevance
“…The CFSE assay was found to be a reliable test system, in agreement with previously reported results 20. We observed a strong inhibitory effect in all tested samples of healthy donors similar to the results of Szczepiorkowski et al 30. In the context of ECP quality control, CD71 was examined for the first time in this study; therefore, no comparative values are available in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…The CFSE assay was found to be a reliable test system, in agreement with previously reported results 20. We observed a strong inhibitory effect in all tested samples of healthy donors similar to the results of Szczepiorkowski et al 30. In the context of ECP quality control, CD71 was examined for the first time in this study; therefore, no comparative values are available in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…The impact of ECP on lymphocyte proliferation is likely less relevant to the mechanism of action, mainly confirming the direct effects of ECP on treated lymphocytes. The trends we observed for both of these parameters in Amicus ECP‐treated cells are in line with values reported for other online and offline systems 18‐20 and meet ECP verification standards proposed by an Italian consensus group 21 and the French regulatory body, ANSM 22…”
Section: Discussionsupporting
confidence: 89%
“…This may in part be due to the rapid kinetics of apoptosis in the ECP‐treated cells from the previous day's procedure. Szczepiorkowski and colleagues recently reported that a median of 92% of ECP‐treated cells are apoptotic after 24 hours of culture when using the Therakos CELLEX device, albeit in healthy subjects 18 . We observed a similarly high median of 86% apoptotic lymphocytes within the same time frame in our cGVHD patient population treated with the Amicus ECP system.…”
Section: Discussionsupporting
confidence: 73%
“…Unanswered questions and future research ECP protocols are usually defined according to the blood volume processed to collect a variable number of MNCs. 12,13 However, the real objective should be a prefixed number of MNCs that we define as the MNC standard dose. This is a quantity of MNCs that has not been determined definitively in any study.…”
Section: Mechanism and Implications For Clinicians And Policymakersmentioning
confidence: 99%